Zonally asymmetric influences of the quasi-biennial oscillation on stratospheric ozone ... - Wang, Wuke; Hong, Jin; Shangguan, Ming; Wang, Hongyue; Jiang, Wei; Zhao, Shuyun (GFZ German Research Centre for Geosciences, 2023)
<!--!introduction!--> While the zonal mean signals associated with the quasi-biennial oscillation (QBO) in stratospheric ozone have been relatively well documented, the zonal (longitudinal) differences have been less studied. Using satellite-based ozone data, ERA5 reanalysis and model simulations, we demonstrate that the influences of QBO on stratospheric ozone and total column ozone (TCO) are seasonally dependent zonally asymmetric. During boreal winter (DJF), positive anomalies of TCO and stratospheric ozone are evident during QBO westerly (QBOW) phases over the regions from North America to the North Atlantic (120˚ W–30˚ E), while significant negative anomalies exist over other longitudes in the Arctic. In boreal autumn (SON), TCO and stratospheric ozone are anomalously high during QBOW from Greenland to Eurasia (60˚ W–120˚ E) but anomalously low in other regions over the Arctic. Weak positive TCO and stratospheric ozone anomalies exist over the South America sector (90˚ W–30˚ E) of the Antarctic, ... : The 28th IUGG General Assembly (IUGG2023) (Berlin 2023) ...